2019
DOI: 10.1002/ijc.32332
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity of Helicobacter hepaticus infection in the lower bowel mucosa of 129/SvEv Rag2−/‐Il10−/−gpt delta mice is influenced by sex

Abstract: Inflammatory bowel disease and colonic tumors induced by Helicobacter hepaticus (Hh) infection in susceptible mouse strains are utilized to dissect the mechanisms underlying similar human diseases. In our study, infection with genotoxic cytolethal distending toxin-producing Hh in 129/SvEv Rag2−/−Il10−/− gpt delta (RagIl10gpt) mice of both sexes for 21 weeks induced significantly more severe cecal and colonic pathology compared to uninfected controls. The mutation frequencies in the infected RagIl10gpt males we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
(157 reference statements)
0
2
0
Order By: Relevance
“…This premise is supported by our previous work illustrating that Hh infection induced more invasive cancer in the lower bowel of Rag2-deficient male mice receiving Il10-deficient regulatory T cells compared to their female counterparts [ 29 ]. In addition, our recent study reported that Hh infection increased genomic mutation frequencies in male but not female Il10-deficient RAG2 gpt mice compared with their respective controls, suggesting that males are more susceptible to genomic mutations promoted by Hh infection [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…This premise is supported by our previous work illustrating that Hh infection induced more invasive cancer in the lower bowel of Rag2-deficient male mice receiving Il10-deficient regulatory T cells compared to their female counterparts [ 29 ]. In addition, our recent study reported that Hh infection increased genomic mutation frequencies in male but not female Il10-deficient RAG2 gpt mice compared with their respective controls, suggesting that males are more susceptible to genomic mutations promoted by Hh infection [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of the three catalytic residues mentioned above were widely used in the literature to abolish the catalytic activity of CdtB. First of all, proliferating cells exposed to a toxin bearing a CdtB mutated in the corresponding DNase I H134 catalytic residue do not suffer DNA damage, cell cycle block or apoptosis, as shown with EcolCDT-I and-II [25,27,51,73,88,89], CjejCDT [12,93], AactCDT [40,64,77] and HparCDT [94]. However, this AactCDT mutant still induces apoptosis in non-proliferating blood cells [40], suggesting that CdtB catalytic activity may not be involved in the observed toxicity.…”
Section: Structure–function Relationshipmentioning
confidence: 99%